Ripples of change: transforming lives and communities through sport in Colombia - Ponciano Núñez, Pedro Danilo; Lyras, Alexis; Matus-Castillo, Carlos; Giakoni-Ramírez, Frano; Duclos-Bastias, Daniel (Frontiers in Sports and Active Living, 2024)
The Colombianitos Foundation (CF) is a pioneering youth development organization that utilizes football as a pedagogical instrument to promote life skills, civic values, and social inclusion in vulnerable communities across Colombia. This study aims to challenge the foundational assumption that sport can catalyze positive change and impart civic values, by investigating the perceived change and efficacy of the CFs Goals for a Better Life program on positive youth development in Colombia. Employing a qualitative research methodology, 28 in-depth interviews with administrators and coaches were conducted, followed by a content analysis to identify thematic patterns. The findings reveal CF's transformative capacity in cultivating human capital, social and societal capital, and distinct programmatic characteristics. CF's interventions foster significant behavioral changes, such as improved conflict resolution and non-violent communication, while promoting essential life skills and social cohesion. Moreover, the study illustrates CF's role in generating a ripple effect, wherein the benefits extend beyond individual participants to their families and the broader community. CF challenges entrenched gender norms through its mixed-gender team structure, aligning with SDG 5, and demonstrates a commitment to fostering peaceful, inclusive societies in line with SDG 16. By grounding its approach in evidence-based evaluation and leveraging strategic partnerships, CF exemplifies a sustainable model of sport-for-development. The study contributes to a deeper understanding of sport's potential to drive long-term social transformation, offering empirical insights for future research and intervention design in post-conflict and marginalized settings.